2022
DOI: 10.1039/d1dt03715c
|View full text |Cite
|
Sign up to set email alerts
|

Tunable TiO2–BN–Pd nanofibers by combining electrospinning and atomic layer deposition to enhance photodegradation of acetaminophen

Abstract: The demand for fresh and clean water sources increases globally, and there is a need to develop novel routes to eliminate micropollutants and other harmful species from water. Photocatalysis is...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 121 publications
1
28
0
Order By: Relevance
“…1.c). This also confirmed that the moderate amount of TiO2 was uniformly distributed in the H95T5 hybrids, as previously reported 39,40,[53][54][55][56][57][58][59][60][61] . To study the sample crystallinity, XRD analysis were carried out.…”
Section: 1morphological and Structural Characterizationsupporting
confidence: 90%
See 4 more Smart Citations
“…1.c). This also confirmed that the moderate amount of TiO2 was uniformly distributed in the H95T5 hybrids, as previously reported 39,40,[53][54][55][56][57][58][59][60][61] . To study the sample crystallinity, XRD analysis were carried out.…”
Section: 1morphological and Structural Characterizationsupporting
confidence: 90%
“…The R2 value of H95T5 (5% of TiO2) increased to 1280 Ω. The R2 of HNT was 6027.8 Ω, which indicates lower recombination rate between electrons and holes and thus, longer electron lifetime 57 .…”
Section: 2electrochemical Activitymentioning
confidence: 94%
See 3 more Smart Citations